Does an Inclusive Citizenship Law Promote Economic Development? - Patrick Imam; Roland Kangni Kpodar (Fondation pour les études et recherches sur le développement international (FERDI), 2018)
This paper analyzes the impact of citizenship laws on economic development. We first document the evolution of citizenship laws around the world, highlighting the main features of jus soli, jus sanguinis as well as mixed regimes, and shedding light on the channels through which they could have differentiated impact on economic development. We then compile a data set of citizenship laws around the world. Using cross-country regressions, panel-data techniques, as well as the synthetic control method and subjecting the results to a battery of tests, we find robust evidence that jus soli laws—being more inclusive—lead to higher income levels than alternative citizenship rules in developing countries, though to a less extent in countries with stronger institutional environment.
Keywords: P16; K40; F22; O15; 330